Higher emotional intelligence is related to lower test anxiety among students - Ahmadpanah M; Keshavarz M; Haghighi M; Jahangard L; Bajoghli H; Sadeghi Bahmani D; Holsboer-Trachsler E; Brand S (Neuropsychiatric Disease and Treatment)
Mohammad Ahmadpanah,1 Mohammadreza Keshavarz,1 Mohammad Haghighi,1 Leila Jahangard,1 Hafez Bajoghli,2 Dena Sadeghi Bahmani,3 Edith Holsboer-Trachsler,3 Serge Brand3,4 1Behavioral Disorders and Substances Abuse, Research Center, Hamadan University of Medical Sciences, Hamadan, Iran; 2Iranian National Center for Addiction Studies (INCAS), Iranian Institute for Reduction of High-Risk Behaviors, Tehran University of Medical Sciences, Tehran, Iran; 3Psychiatric Clinics of the University of Basel, Center for Affective, Stress and Sleep Disorders, 4Department of Sport, Exercise and Health Science, Sport Science Section, University of Basel, Basel, Switzerland Background: For students attending university courses, experiencing test anxiety (TA) dramatically impairs cognitive performance and success at exams. Whereas TA is a specific case of social phobia, emotional intelligence (EI) is an umbrella term covering interpersonal and intrapersonal skills, along with positive stress management, adaptability, and mood. In the present study, we tested the hypothesis that higher EI and lower TA are associated. Further, sex differences were explored.Method: During an exam week, a total of 200 university students completed questionnaires covering sociodemographic information, TA, and EI.Results: Higher scores on EI traits were associated with lower TA scores. Relative to male participants, female participants reported higher TA scores, but not EI scores. Intrapersonal and interpersonal skills and mood predicted low TA, while sex, stress management, and adaptability were excluded from the equation.Conclusion: The pattern of results suggests that efforts to improve intrapersonal and interpersonal skills, and mood might benefit students with high TA. Specifically, social commitment might counteract TA. Keywords: test anxiety, emotional intelligence, students, interpersonal skills, intrapersonal skills